Jaringan Aktor Dalam Pemberdayaan Masyarakat Pada Program Kota Tanpa Kumuh (KOTAKU) Di Kelurahan Pasar II Kecamatan Prabumulih Utara Kota Prabumulih Provinsi Sumatera Selatan - Afdil Hafidh; Eva Lidya (Jurnal Empirika, 2019)
This study research aims to (1) know the background formation, and (2) knowing the business management process of 212 Mart in Palembang. This study research was a descriptive qualitative. the data types and sources obtained through primary data and secondary data with data collection techniques in the form of observations, interviews and documentation. This study research uses Transformation of Habraken's perspective theory. The results of this study indicate that (1) a desire arises to introduce and develop a business based religion to compensate for the spread of conventional minimarkets. Begins from business introduction develops into an awareness for resource management of human mobility. The Lifestyle changes occur due to environment influence that this facilitates are group needs within a religion based business; (2) The management process with a congregational system facilitate business implementation in adopting technology and fashion conventional minimarket. The Implementation of religious values makes a portion of the business results is given to the interests of the people (almsgiving, zakat and the development of da'wah). Marketing problems can be resolved by enforcing mandatory spending monthly at 2,468 investors.